Neurometabolic Disorders-Related Early Childhood Epilepsy: A Single-Center Experience in Saudi Arabia - Sarar Mohamed; Ebtessam M. El Melegy; Iman Talaat; Amany Hosny; Khaled K. Abu-Amero (Pediatrics and Neonatology)
Data on the pattern of epilepsy caused by metabolic disorders in the first 2 years of life are limited in developing countries. We aimed to identify the metabolic causes of epilepsy presented in the first 2 years of life and to describe their clinical, radiological, molecular, and electroencephalographic characteristics. Methods: This retrospective study was conducted between January 2010 and December 2011 at Saad Specialist Hospital (Al Khobar, Saudi Arabia). All patients younger than 2 years at the onset of epilepsy caused by metabolic disorders were reviewed. The International League Against Epilepsy definition was used, and febrile convulsion was excluded. Results: Of 221 children diagnosed with epilepsy in the first 2 years of life at our hospital, 24 had metabolic diseases. The characteristics of these 24 children included the following: consanguinity in 18 patients (75%), developmental delay in 13 (54%), generalized tonic–clonic seizures in 10 (42%), infantile spasms in four (17%), myoclonic in seven (29%), and focal seizures in three. The diagnosis was confirmed by DNA studies in 17 patients (71%) and enzyme assay in seven (29%). The main diagnoses were peroxisomal disorders (n = 3), nonketotic hyperglycinemia (n = 3), Menkes disease (n = 2), neuronal ceroid lipofuscinosis (n = 2), biotinidase deficiency (n = 2), and mitochondrial disorder (n = 2). The remaining patients had lysosomal storage disease, aminoacidopathy, fatty acid oxidation defects, and organic aciduria. Seizure freedom was achieved in one third of patients in this cohort. Conclusion: Different metabolic disorders were identified in this cohort, which caused different types of epilepsy, especially myoclonic seizures and infantile spasms.